Foucault - maoismen, genealogien - Karlsen, Mads Peter; Villadsen, Kaspar (Slagmark - Tidsskrift for idéhistorie, 2018)
Foucault’s inspiration from Nietzsche in terms of his approach to the writing of history is difficult to overestimate. However, this article will advance an interpretation of Foucault’s approach to history which focuses on another, and less readily evident, dialogue partner in his authorship, namely the Marxist tradition and, more precisely, French Maoism. In the first part it is argued that Foucault’s practical experience from his involvement in the Maoist inspired activist group, Groupe d’information sur les prisons (GIP), left crucial marks on his contemporaneous statements on the genealogical method and his elaboration of the power-knowledge nexus. In the second part of the article it is demonstrated how the activism of GIP is reflected in his lectures at Collège de France in 1976. The aim of the article is threefold. Firstly, to bring attention to other (largely neglected) sources of inspiration for Foucault’s genealogical approach than Nietzsche. Secondly, to contribute to a more nuanced understanding of Foucault’s relationship to Marxism, which is frequently portrayed rather one-sidedly as unambiguously negative. And thirdly, to demonstrate concretely how principles originating from Maoist political activism reappear, not only in Foucault’s practical commitment to GIP, but also in his theoretical considerations of genealogy.